Navigating students' hurdles and coping mechanisms amidst the COVID-19 pandemic in teaching and learning methods - Ismail, Aida Hazlin; Abd Hamid, Nadiah; Abd Rasit, Zarinah (Faculty of Administrative Science and Policy Studies, 2025)
This study examines the perceptions of accounting students at Universiti Teknologi MARA Kampus Puncak Alam regarding online learning and teaching, particularly in the context of the COVID-19 pandemic. The pandemic necessitated a rapid shift from traditional face-to-face classes to online education, prompting a global transition in higher education. The research focuses on the challenges, coping mechanisms, and experiences of students as they navigate this new learning environment. A qualitative, open-ended survey methodology was employed, targeting 153 Bachelor of Accountancy students with at least one semester of online learning experience. The survey aimed to gather in-depth insights into students' attitudes toward the effectiveness and accessibility of online learning, as well as the technological barriers they encountered, such as limited internet connectivity and inadequate learning resources. The results revealed both positive aspects of online learning, such as flexibility and accessibility, as well as significant challenges, including the lack of social interaction and technical difficulties. Despite these obstacles, students developed various coping strategies, including time management, online study groups, and seeking emotional support, to manage their academic responsibilities. The study contributes valuable insights into the evolving landscape of online education in Malaysia and provides recommendations for enhancing the online learning experience for future cohorts.